Hot corrosion behavior of APS YSZ coatings treated by laser micro glazing (LMG) under molten salts (V2O5 +Na2SO4). (December 2022) - Huo, Kun; Dai, Fengze; Qian, Wei; Ye, Yunxia; Cai, Jie; Hua, Yinqun; Zhang, Xiaofeng
Abstract: In this study, yttria-stabilized zirconia (YSZ) coatings prepared by atmospheric plasma spraying (APS) were glazed by a nanosecond pulsed laser (laser micro glazing, LMG). The hot corrosion mechanism of as-sprayed, ground, and LMGed YSZ coatings was investigated at a temperature of 1100 ºC in V2 O5 and Na2 SO4 molten salts for 20 h. The results show that a dense LMGed layer with narrow network of segmented microcracks (sub-micron level) was formed after the LMG process. Compared to the single-time LMG, pores can be effectively eliminated after six-times laser irradiation. The hot corrosion behavior of YSZ coatings exposed to molten V2 O5 +Na2 SO4 demonstrates that pores in the single-time LMGed layer seriously affect its hot corrosion resistance. After multiple LMG, the volume fraction of the m-ZrO2 decreases from 53% to 27% with the disappearance of pores. The quantity of the corrosion products YVO4 was greatly reduced and the depth of the damaged area diminished from 37.073 µm to 20.918 µm, which shows a significant improvement in molten salts corrosion resistance. Highlights: A thin laser micro glazed (LMGed) layer was fabricated by a nanosecond pulsed laser. Extremely narrow mircocracks were formed (sub-micron level) in LMGed layer. Proes were eliminated by laser multiple times scanning. Reduction of roughness from Ra 6.704 µm to Ra 2.890 µm by LMG process. Up factors lead to an improvement in hot corrosion resistance of LMGed coatings.